John Haynes Holmes papers - Holmes, John Haynes, 1879-1964.; Holmes, John Haynes, 1879-1964.; Holmes, John Haynes, 1879-1964.
Correspondence, writings, printed matter, and other papers relating to Holmes's public career and to the libertarian movements of the 20th century. Documents his involvement with civil liberties, civil rights, pacifism, and social service organizations including the American Civil Liberties Union, American Friends Service Committee, Council Against Intolerance in America, Foster Parents' Plan for War Children, League for Industrial Democracy, National Association for the Advancement of Colored People, Planned Parenthood Federation of America, and War Resisters League. Also includes material pertaining to his activities as pastor of the Church of the Messiah (later Community Church), New York, N.Y., and to his personal life. Subjects include abortion, African Americans, birth control, civil society, contraception, economic conditions, economic policy, industrial policy, industry, labor, labor unions, peace, prejudices, race relations, racism, social conditions, social values, Society of Friends, toleration, and World War II refugee children. The writings file includes Holmes's articles, hymns, sermons, and manuscripts of his books including My Gandhi (1953) and I Speak for Myself: The Autobiography of John Haynes Holmes (1959).
Correspondents include Roger N. Baldwin, Henry Beckett, Arthur E. Calder, Carl Colodne, Ethelwyn Doolittle, Donald Szantho Harrington, Arthur Garfield Hays, Arthur Heller, B.W. Huebsch, Fiorello H. La Guardia, Corliss Lamont, Lillian Laub, Salmon Oliver Levinson, Minnie Loewenthal, Louis B. Mayer, George E. Moesel, Francis Neilson, Carl Nelson, Edith Lovejoy Pierce, Henriette Posner, Ralph C. Roper, Norman Thomas, Carl Hermann Voss, Blanche Watson, and Walter Francis White.
Holmes's autograph collection contains copies of letters from individuals including John Dewey, Mahatma Gandhi, Herbert Hoover, Helen Keller, Charles A. Lindbergh, Jawaharlal Nehru, Eddie Rickenbacker, Bertrand Russell, and Wendell L. Willkie.
Microfilm edition of containers 177-269 available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Unitarian clergyman and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Baldwin, Roger N. -- 1884-1981 -- Correspondence; Beckett, Henry -- Correspondence; Calder, Arthur E. -- Correspondence; Colodne, Carl -- Correspondence; Dewey, John, -- 1859-1952 -- Correspondence; Doolittle, Ethelwyn -- Correspondence; Gandhi, Mahatma, -- 1869-1948 -- Correspondence; Harrington, Donald Szantho -- Correspondence; Hays, Arthur Garfield, -- 1881-1954 -- Correspondence; Heller, Arthur -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; Huebsch, B. W. -- 1876-1964 -- Correspondence; Keller, Helen, -- 1880-1968 -- Correspondence; La Guardia, Fiorello H. -- 1882-1947 -- Correspondence; Lamont, Corliss, -- 1902-1995 -- Correspondence; Laub, Lillian -- Correspondence; Levinson, Salmon Oliver, -- 1865-1941 -- Correspondence; Lindbergh, Charles A. -- 1902-1974 -- Correspondence; Loewenthal, Minnie -- Correspondence; Mayer, Louis B. -- 1885-1957 -- Correspondence; Moesel, George E. -- Correspondence; Nehru, Jawaharlal, -- 1889-1964 -- Correspondence; Neilson, Francis, -- 1867- -- Correspondence; Nelson, Carl, -- 1915 or 1916- -- Correspondence; Pierce, Edith Lovejoy, -- 1904- -- Correspondence; Posner, Henriette -- Correspondence; Rickenbacker, Eddie, -- 1890-1973 -- Correspondence; Roper, Ralph C. -- Correspondence; Russell, Bertrand, -- 1872-1970 -- Correspondence; Thomas, Norman, -- 1884-1968 -- Correspondence; Voss, Carl Hermann -- Correspondence; Watson, Blanche -- Correspondence; White, Walter Francis, -- 1893-1955 -- Correspondence; Willkie, Wendell L. -- 1892-1944 -- Correspondence; American Civil Liberties Union; American Friends Service Committee; Church of the Messiah (New York, N.Y.); Community Church (New York, N.Y.); Council Against Intolerance in America; Foster Parents' Plan for War Children; League for Industrial Democracy; National Association for the Advancement of Colored People; Planned Parenthood Federation of America; War Resisters League; Abortion; African Americans; Birth control -- United States; Civil rights -- United States; Civil society -- United States; Contraception; Hymns; Industrial policy -- United States; Industries -- United States; Labor and laboring classes -- United States; Labor unions -- United States; Libertarianism -- United States; Pacifism; Peace; Prejudices; Racism -- United States